2D Materials Based on Main Group Element Compounds: Phases, Synthesis, Characterization, and Applications. (9th August 2020) - Lu, Ziyang; Neupane, Guru Prakash; Jia, Guohua; Zhao, Haitao; Qi, Dongchen; Du, Yaping; Lu, Yuerui; Yin, Zongyou
Abstract: 2D materials based on main group element compounds have recently attracted significant attention because of their rich stoichiometric ratios and structure motifs. This review focuses on the phases in various 2D binary materials including III–VI, IV–VI, V–VI, III–V, IV–V, and V–V materials. Reducing 3D materials to 2D introduces confinement and surface effects as well as stabilizes unstable 3D phases in their 2D form. Their crystal structures, stability, preparation, and applications are summarized based on theoretical predictions and experimental explorations. Moreover, various properties of 2D materials, such as ferroelectric effect, anisotropic optical and electrical properties, ultralow thermal conductivity, and topological state are discussed. Finally, a few perspectives and an outlook are given to inspire readers toward exploring 2D materials with new phases and properties. Abstract : 2D materials based on main group element compounds exhibit rich stoichiometries and structure motifs. The synthesis of these multiphase materials is controllable using new methodologies. Furthermore, their properties are revealed based on theoretical predictions and experimental exploration, and then developed for various potential applications.